Presence of the matrix metalloproteinases during the migration of the primordial germ cells in zebrafish gonadal ridge - Mazzoni, Talita Sarah [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Springer Nature, 2021)
In vertebrates, the primordial germ cells (PGCs) differentiate from extragonadal regions, migrating to gonadal ridge during the embryonic development. However, recent studies in mammals indicate that the PGCs originate from the epiblast and subsequently migrate into the yolk sac. Cell and molecular bases involved in routes during the migration of these cells are still not well understood. Thus, in an attempt to evaluate the participation of matrix metalloproteinases (MMPs) during the gonadal primordium formation in Danio rerio (zebrafish), the route of migration of PGCs was analyzed. In zebrafish, during the migration of the PGCs to the forming gonad, they bind by cytoplasmic processes to the extracellular matrix and migrate through amoeboid movements until they reach the gonadal ridge. During the epiboly, MMPs were not detected. However, after organogenesis, three MMP types were expressed in the somatic cells that were located ahead of the PGCs in the migration route. This expression was maintained throughout the mesentery and was not detected in the PGCs. Upon reaching the gonadal ridge, the PGCs and somatic cells express MMPs and epithelium begins to be formed. After the formation of the basement membrane, the germinal epithelium is delineated by the somatic cells, which remodeling the extracellular matrix. So, a PGC organization occurs through the tissue, forming the gonadal primordium. Concomitantly, granulocytes expressing different MMPs are present. This data in exposing the role of MMPs during the PGC migration to the forming gonad, may point a new way in understanding the reproductive biology of the vertebrates in general.
Keywords: Danio rerio; Gelatinases; Gonadal morphogenesis; Gonocytes; vasa gene